Oral Health Behaviors and Perceptions Among College Students. Issue 4 (October 2016) - Crabtree, Rebecca; Kirk, Abigail; Moore, Moriah; Abraham, Sam
Abstract : Oral health is a simple and important part of college students' lives but might often be overlooked or undermined because of increased stress levels and unhealthy habits associated with the college setting. Despite the challenges, college days may be one of the best times to establish lifelong healthy habits, including oral health routines. The purpose of this study was to determine the current oral care behaviors and perceptions of students at a midwestern college. This study was nonexperimental in nature with a quantitative method and a cross-sectional design, which included 126 participants. The survey instrument included 2 Likert-type scales. The oral health–related quality-of-life model was used as the theoretical framework to guide the study.